Habitat suitability analysis of Dendrobium flexicaule using MaxEnt and InVEST models - Lin, Wei; Ye, Chenjuan; Ming, Xingjia; Qi, Junsheng; Liu, Xiang; Fan, Guochun; Liao, Jiaxin; Wang, Yongde; Liu, Xue (Frontiers in Plant Science, 2025)
IntroductionDendrobium flexicaule, an orchid endemic to China, is valued in Traditional Chinese Medicine; however, its conservation and sustainable use lack spatial guidance.MethodsThis study employed the MaxEnt model to predict suitable habitats for D. flexicaule under varying climatic conditions. Building upon the high-suitability areas identified by MaxEnt, we further utilized the InVEST model to delineate high-quality habitat zones as key areas for conservation and development planning.ResultsResults revealed that D. flexicaule is primarily found in Sichuan, Chongqing, Guizhou, Henan, and Hubei. Future scenarios suggest an expansion of suitable habitats, with precipitation, temperature, and slope emerging as the dominant environmental drivers. Priority conservation zones cluster along the southern and the eastern edge of the Qinba Mountains, whereas priority development areas concentrate in the northern foothills of the Qinba Mountains.DiscussionOur analysis highlighted the critical influence of precipitation and temperature on the species’ distribution, ultimately identifying priority conservation areas. This integrated approach provides a scientific foundation for the sustainable development of D. flexicaule.